Glycoprotein Ibα and von Willebrand factor in primary platelet adhesion and thrombus formation: Lessons from mutant mice - Bergmeier, Wolfgang; Chauhan, Anil K.; Wagner, Denisa D. (Thrombosis and Haemostasis, 2008)
The von Willebrand factor (VWF) receptor complex, glycoprotein (GP)Ib-V-IX, and its main ligand VWF play a key role in the adhesion process of platelets to sites of vascular injury. Recent studies in mutant mice have shed new light on the importance of either molecule for the development of arterial and venous thrombosis. In this review, we summarize the most important aspects from these studies.
Keywords: Thrombosis; glycoprotein; vonWillebrand factor; mutant; mice